(untitled) (Genius Repository, 2023)
This article is devoted to the problem of personality disposition. Dispositions manifest themselves everywhere in various spheres of human life. Their manifestation in the educational environment has a certain specificity, which largely determines the characteristics of behavior and the quality of educational activities. The article presents the results of the study.